A review on thermal stability and high temperature induced ageing mechanisms of solar absorber coatings. (January 2017) - Zhang, Ke; Hao, Lei; Du, Miao; Mi, Jing; Wang, Ji-Ning; Meng, Jian-ping
Abstract: Many novel, efficient solar absorber coatings are developed in recent decades. However, the methods of qualification tests, such as test of thermal stability, corrosion resistance and prediction of service life that have important engineering significance for solar absorbers to be large-scale applications, are still lacking. Currently, European standard (EN 12975-3-1) and International standard (ISO/CD 12592, 2) are usually applied in conventional situations, such as low- to mid- temperature, slight moisture and sulphur dioxide. However, many other developing industrial countries may face a tougher circumstance, for instance, acid rain, salt mist, sandstorm, smog etc. Therefore, resulting in more complicated ageing mechanisms that the European standard and International standard are no longer well suited. As for the current thermal stability test methods. The customized test method are usually adopted to evaluate the coatings durability during research stage. And the standard test method mainly used to predict the service lifetime for low- to mid- temperature applications. The current problem is how to make up the scarcity of standard test procedure for performance evaluation of high-temperature solar absorber coatings. As for the ageing mechanisms, the most common ageing mechanisms under high temperature are diffusion and oxidation of elements. But, more details on the thermal stability and micro behaviours including element diffusion and distribution, chemical interaction, crystal transition, the surface and cross section ageing morphology of different solar absorber coatings, are still worthy of in-depth study. This paper reviews various solar absorber coatings and thermal stability test methods, evaluates the temperature induced ageing mechanisms, and discusses several commercial applications and challenges in protect the solar absorber coatings. The purpose of this review is to discuss the thermal stability and underlying ageing process of some popular coatings, and the scope for performance improvement. In addition, this paper addresses the new concept of graphene solar absorber coatings.